Spatial Map Of Hygiene Risk And Infection Of Soil-Transmitted Helminths In Stunting Toddlers In Kaliwates - Yunita Armiyanti; Dimas Aji Bimantara; Azham Purwandhono; Achmad Maududie; Wiwien Sugih Utami; Bagus Hermansyah (Window of Health : Jurnal Kesehatan, 2026)
Soil-transmitted helminths remain major neglected tropical infections affecting approximately 24% of the global population, particularly in areas with poor sanitation and hygiene. Chronic infection may contribute to malnutrition and stunting in children. This study aimed to analyze the spatial distribution of soil-transmitted helminth infections and hygiene risk among stunted toddlers in Kaliwates District. A cross-sectional study was conducted from August 2023 to May 2024 involving 103 stunted toddlers. Stool samples were examined using sedimentation and flotation methods, and hygiene data were collected through caregiver interviews. Fisher’s exact test and Moran’s Index were applied. The infection prevalence was 8.7%, predominantly hookworm. No significant association was found between hygiene factors and infection (p>0.05). Spatial analysis indicated a random distribution pattern. These findings suggest that deworming programs and hygiene promotion should be maintained, and spatial mapping may support targeted interventions.